2015
DOI: 10.1111/cas.12817
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic strategies targeting cancer stem cells

Abstract: Cancer stem cells (CSCs) are undifferentiated cancer cells with a high tumorigenic activity, the ability to undergo self‐renewal, and a multilineage differentiation potential. Cancer stem cells are responsible for the development of tumor cell heterogeneity, a key feature for resistance to anticancer treatments including conventional chemotherapy, radiation therapy, and molecularly targeted therapy. Furthermore, minimal residual disease, the major cause of cancer recurrence and metastasis, is enriched in CSCs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
178
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(180 citation statements)
references
References 83 publications
2
178
0
Order By: Relevance
“…The CSC model has been proposed to explain the high rate of relapse and subsequent resistance of cancer to current systemic treatments [25]. CSCs have been identified in many solid malignancies, including gastric cancer, and have significant clinical implications, as targeting the CSC population may be essential in preventing the recurrence and spread of a tumour [26, 27]. Herein, we found that miR-501-5p acted as a potent CSC-promoting factor in GC.…”
Section: Discussionmentioning
confidence: 76%
“…The CSC model has been proposed to explain the high rate of relapse and subsequent resistance of cancer to current systemic treatments [25]. CSCs have been identified in many solid malignancies, including gastric cancer, and have significant clinical implications, as targeting the CSC population may be essential in preventing the recurrence and spread of a tumour [26, 27]. Herein, we found that miR-501-5p acted as a potent CSC-promoting factor in GC.…”
Section: Discussionmentioning
confidence: 76%
“…This extremely tumorigenic subpopulation of cells at the top of the hierarchy consists of cancer stem cells (CSCs) and generates progenitors and cells at different levels of differentiation along a variety of lineages [5].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer stem cells are also responsible for the development of tumor cell heterogeneity which is often related to the failure of conventional therapies [5]. Therefore, targeting CSCs is critical for developing innovative therapies to counteract cancer relapse and emergence of drug resistance [6].…”
Section: Introductionmentioning
confidence: 99%
“…As cancer stem cells seem to be the most resistant to conventional therapy, it is important to develop new strategies to combat them 9, 10. Indeed, malignancies may develop not only as the consequence of gene mutations but also as a result of epigenetically deregulated development of stem cells of which germ cell tumours are the best example 11, 12, 13.…”
Section: Introductionmentioning
confidence: 99%